A contextual analysis of pupil-involving oculomotor nerve palsies in two Tertiary Hospitals in Johannesburg, South Africa - Erasmus, Clayton Burt (My University, 2018)
Purpose: To analyse the sensitivity of computed tomography angiography (CTA) in ruling out intracranial aneurysm in patients presenting with pupil-involving oculomotor nerve palsy and to describe the demographics of these patients presenting to Johannesburg’s Academic Hospitals. Methods: All patients presenting within a 40-month period with pupil-involving third nerve palsy that went on to have a proven posterior communicating artery (PcomA) aneurysm were looked at retrospectively to ascertain whether the initial CTA revealed the correct diagnosis, or if the aneurysm was detected when the patient went for cerebral catheter angiography (CCA) in the form of 3D rotational digital subtraction angiography (3DR DSA). The size of aneurysms causing third nerve palsy was analysed according to measurements ascertained from DSA reports. The demographics of patients with pupil-involving third nerve palsies were analysed, which included age, gender and race. Other clinical presentations of PcomA aneurysms were analysed as above and reported on separately. Results: A total of 15 cases of isolated pupil-involving third nerve palsy were recorded, of which 13 (86.7%) had proven PcomA aneurysm on DSA. The sensitivity of CTA was calculated to be 76.9% (p < 0.1)) with a total of 10 of the proven 13 PcomA aneurysms detected on initial CTA. The mean aneurysm diameter in the pupil-involving third nerve group was found to be 8.5mm. The population mean age was calculated to be 44.2 years with 87% of this group comprising of females. The total number of patients found to have PcomA aneurysm when including other clinical presentations was 28, with the overall sensitivity of CTA calculated as 82.1% (p ˂ 0.02). Conclusions: The sensitivity for detecting posterior communicating artery aneurysms on CTA is not adequate. The gold standard for imaging intracranial aneurysms remains CCA with DSA in our setting. Symptomatic aneurysms were found to be greater than 3 – 4mm and CTA detection was more sensitive for larger aneurysms.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Ophthalmology Completed and submitted April 2018, Johannesburg.
Keywords: Oculomotor Nerve Diseases